Photodegradation of sparfloxacin and isolation of its degradation products by preparative HPLC - Salgado, Hérida Regina Nunes [UNESP]; Moreno, P. R. H.; Braga, A. L.; Schapoval, E. E. S. (My University, 2005)
Sparfloxacin, a third generation fluoroquinolone derivative, is a potent antibacterial agent active against a wide range of Gram-positive and Gram-negative organisms including Streptococcus pneuinoniae, Staphylococcus aureus, methicillin resistant S. aureus, Legionella spp., Mycoplasina spp., Chlamydia spp. and Mycobacterium spp. A drawback of fluoroquinolones is their photoreactivity. Sparfloxacin has been studied in terms of therapeutic activities. However, there are few published of analytical methods being applied to sparfloxacin. The aim in this study was to determine the photodegradation products of sparfloxacin, when submitted to UV light, and to characterize two of these products, designated SPAX-PDP1 and SPAX-PDP2. An accelerated study of stability in methanol solution was carried out by exposing a solution of sparfloxacin to UV light (peak wavelength 290 nm) for 36 hours at room temperature. The products were analyzed by NMR spectrophotometry, IR spectrometry and mass spectrophotometry. The results suggest that the products isolated here could be used to estimate the degradation of sparfloxacin in a stability study. However, the low activity exhibited by UV-irradiated sparfloxacin is a source of concern that demands further investigation of the mechanism of its photodegradation mechanism.
Keywords: Degradation products; Fluoroquinolone; Photodegradation; Quality control; Sparfloxacin; Stability; drug metabolite; methanol; sparfloxacin; sparfloxacin pdp1; sparfloxacin pdp2; unclassified drug; antibacterial activity; carbon nuclear magnetic resonance; drug isolation; drug mechanism; drug structure; Gram negative bacterium; Gram positive bacterium; high performance liquid chromatography; infrared spectrometry; mass spectrometry; nonhuman; photodegradation; proton nuclear magnetic resonance; room temperature; ultraviolet radiation